Assessing the Influence of Source Characteristics, Psychological-Related Factors, and Content Attributes on Purchase Intention: The Case of an International Cosmetics Company in the Philippines - Tanpoco, Manuel R.; Alonte, Alexis Therese L.; Nubla, Candace Anne D.; de Arellano, Dominique Marie B. Ramirez; Torres, Ralph Phillip F.; Caminong, Joliber M.; Morales, Retchell Rubin L. (Future Science / FSH-PH Publications, 2023)
Influencer Marketing has become a widely used strategy wherein social media influencers partner with businesses to create awareness about their brand and promote their products. XYZ (not real name) Cosmetics, an international cosmetics company that provides affordable, high-quality products to the Philippine market, is one such company that embraces the trend. It has integrated influencer marketing to better connect with its customers. This study determines the relationship between the three aspects of influencers: Source Characteristics (Attractiveness and Popularity), Psychological-Related Influential Factors (Self-Congruency and Product Match-Up), and Content Attributes (Quality and Uniqueness) with XYZ's Customer Purchase Intention (CPI). Through using a case study survey research design, the study chose 387 respondents, randomly sampling the Instagram followers of XYZ. An online questionnaire consisting of seven-point Likert scale items was administered. The results show that Attractiveness, Uniqueness, and Self-Congruency significantly affect customer purchase intention, while Popularity, Product Match-up, and Quality do not. The study has implications for brand managers and entrepreneurs, underscoring how an influencer should be selected, especially for cosmetics companies like XYZ. The researchers recommend choosing an attractive and unique influencer known to possess credibility, an amiable personality, and good values while focusing less on assessing how well the influencer vlogs, how popular the talent is, and how matched the person is with the company's products.